School Health Needs Assessment in Chanchamayo, Peru: A Health Promoting School Project - Choi, Yoona; Kang, Sunjoo; Kim, Jin Sun; Kwon, Insook; Lee, Myungken (Frontiers in Public Health, 2020)
Background: School-based health promotion can be particularly valuable in developing countries. However, there is a lack of information about health needs of Peruvian school students. The purpose of this study was to conduct a health needs assessment to develop strategies for a school health promotion program in a jungle and indigent region in Chanchamayo, Peru. Methods: This study was conducted using a mixed method approach that included a literature review, national and local statistics, stakeholder interviews, and a survey. Participants of the survey were 210 teachers, 2,504 elementary school students, and 2,834 secondary school students from six schools in two planned project implementation regions. A self-administered questionnaire for students was developed based on WHO’s Global School-based Student Health Survey. Collected data were analyzed using descriptive statistics, chi-square tests, and t-tests for the survey data and content analysis for the interviews. Results: Weak school health systems were identified, including school health policies, curriculum, trained health care personnel, and health-related facilities and equipment. Common health problems of students were anemia, nutritional deficiency, infectious diseases, tuberculosis, drug abuse, poor hygiene, and sex-related problems. High absence rates from school due to family problems and high dropout rates due to pregnancy were also critical issues. Teachers identified personal hygiene, nutrition, reproductive health, and sex education as high priorities for school health education, while students identified prevention of infectious diseases, nutrition education, psychological health, and healthy life styles as priorities. Identified strategies included: establishment of school health policies, curriculum-based interventions, increasing community participation and raising school health awareness, capacity building for health care promotors, training of trainers, and partnership between schools and communities. Conclusions: Findings from this study will help guide the development and implementation of a school-based health promotion program in Chanchamayo. Multicomponent school-based interventions that consider feasibility and sustainability will be developed and evaluated based on WHO’s Health Promoting School concepts.